Data "Underlying data set for Collings et al 2025_Impact of growing temperature on spear and root carbohydrate content and the effects on postharvest asparagus tip breakdown incidence" - Collings, Emma R.; Alamar, M. Carmen; Terry, Leon A. (Cranfield University, 2025)
Tip breakdown has been identified as the main issue causing deterioration in asparagus quality during storage; however, the underlying mechanisms responsible for its development are unknown. Previous work showed higher incidence of tip breakdown occurring later in the season, when growing temperature is higher. To further our understanding and identify potential biomarkers of this physiological disorder, spears from two growing conditions (cooler vs. warmer), were harvested through the season to assess tip breakdown incidence, and quality attributes (asparagine and non-structural carbohydrates) during storage. Rapid growth due to warmer temperatures (up to 45°C) resulted in spears with lower sugar content and higher incidence of tip breakdown compared to cooler conditions. Asparagine slowly increased through the season (7 to 11 mg g-1 DW) with no differences between growing condition suggesting it is not a biomarker for tip breakdown. Pre-season spears (warm temperature only) had double the amount of sugar compared to early-season spears, with no incidence of tip breakdown despite an extended storage period (up to 18 days at 7°C). Sugar concentrations in roots were similar between growing conditions and between pre- and early-season despite clear differences in spear sugar content. These results showed a strong positive link between cooler growing conditions, high spear sugar content and low susceptibility to tip breakdown which was not reflected in root sugar concentrations.
Raw data set for tip breakdown percentages in asparagus spears are shown for each season, grade, growing condition and storage time. Sugar data in asparagus roots and spears are to follow.
Keywords: Asparagus officinalis; asparagine; sugars; storage